PERENCANAAN ANGGARAN, KUALITAS SUMBER DAYA MANUSIA, PELAKSANAAN ANGGARAN DAN KOMITMEN ORGANISASI PADA PENYERAPAN ANGGARAN : BUDGET PLANNING, QUALITY OF HUMAN RESOURCES, BUDGET EXECUTION, AND ORGANIZATIONAL COMMITMENTS ON BUDGET ABSORPTION - Nursela, Nursela; Taufik, Taufeni; Yasni, Hariadi (Universitas Riau, 2022)
The low level of budget absorption is oftten a problem for Regional Apparatus Organizations (OPD). The research is conducted to describe the effect of budget planning, the quality of human resources, budget execution and organizational commitment to the absorption of regional revenue and expenditure budgets in the Regional Apparatus Organizations of Pelalawan Regency. The population in this study were all OPD in Pelalawan Regency. Sample selection using purposive sampling method. Data was collected by distributing questionnaires to 84 respondents, and only 78 questionnaires could be used in this study. The data analysis method used is Multiple Linear Regression using SPSS version 22. The results showed that budget planning, quality of human resources, budget execution and organizational commitment had an effect on the level of budget absorption in the OPD Pelalawan Distrik. The results of this study have a contribution to the OPD increasing the absorption of regional revenue and expenditure budget.